2009
DOI: 10.1111/j.1365-246x.2009.04163.x
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic observations of the ongoing Dabbahu rifting episode: new dyke intrusions in 2006 and 2007

Abstract: SUMMARY A 60‐km‐long dyke intruded the Dabbahu segment of the Nubia–Arabia Plate boundary (Afar, Ethiopia) in 2005 September, marking the beginning of an ongoing rifting episode. We have monitored the continuing activity using Satellite Radar Interferometry (InSAR) and with data from Global Positioning System (GPS) instruments and seismometers deployed around the rift in response to the initial intrusion. These data show that a sequence of new dyke intrusions has reintruded the central and southern section of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(150 citation statements)
references
References 55 publications
6
144
0
Order By: Relevance
“…Along the rift axis the graben is disrupted by the volcanic topography associated with the Ado Ale Volcanic complex (AVC), a series of faulted silicic lavas flows/domes on the rift flanks and a basaltic volcano at the rift axis with a summit crater, and at its northern end the Dabbahu volcano, which has been active since at least B80 ka (refs 25 and (S. Medynski personal communication)). Seismic [11][12][13] and geodetic [14][15][16][17] observations of the recent dyking events are consistent with a magma source located in the rift centre below the AVC. This central volcanic region also marks a division in the width and morphology of the axial graben and rift flanks between the southern (graben B8 km wide, scarps B100 m high, significant flank topography) and northern (graben B4 km wide, scarps B30-50 m high, smooth flank profile) sectors (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Along the rift axis the graben is disrupted by the volcanic topography associated with the Ado Ale Volcanic complex (AVC), a series of faulted silicic lavas flows/domes on the rift flanks and a basaltic volcano at the rift axis with a summit crater, and at its northern end the Dabbahu volcano, which has been active since at least B80 ka (refs 25 and (S. Medynski personal communication)). Seismic [11][12][13] and geodetic [14][15][16][17] observations of the recent dyking events are consistent with a magma source located in the rift centre below the AVC. This central volcanic region also marks a division in the width and morphology of the axial graben and rift flanks between the southern (graben B8 km wide, scarps B100 m high, significant flank topography) and northern (graben B4 km wide, scarps B30-50 m high, smooth flank profile) sectors (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Observations of the multiple (B14) dyke intrusions 3,[11][12][13][14][15][16][17] and fissure eruptions 18 during this active phase have shown that in the upper part of the crust, the delivery of melts to the DMH rift zone is currently strongly focused along the rift axis. The overall scale and morphology of this B15 Â 60 km magmatic segment is similar to a slow (B20 mm per year) spreading mid-ocean-ridge segment 6 , such as those found along the Mid-Atlantic ridge 19,20 , and the recent episodic rifting activity is similar to that previously observed in Iceland 4,21 .…”
mentioning
confidence: 99%
“…Despite the sometimes-spectacular displacements observed at the surface, the dike-induced fault slip accounted for less than 10% of the total deformation (e.g., Grandin et al, 2009;Wright et al, 2006). The temporal migration of seismicity during the event suggests that the majority of the intrusion was fed laterally from the Ado'Ale volcanic complex (AVC) located at the centre of the segment , with geodetic data suggesting that the magma reservoir feeding the intrusion is~10 km deep (e.g., Hamling et al, 2009).…”
Section: The 2005-2011 Dabbahu-manda-harraro Rifting Episodementioning
confidence: 99%
“…In addition of the geometric complementarity of the measurements, the GPS technique allows the quantification of the relative plate motion while the InSAR technique gives access to deformation across small-scale structures. However, while InSAR showed its potential for studying large amplitude displacements in Afar, such as the dyke sequence along the MH-D rift segment (Wright et al 2006;Grandin et al 2009;Hamling et al 2009), the measurement of small amplitude displacement is complex due to the turbulent tropospheric signal, except in the case of very large SAR image data set, such as the 11-yr-long archive of Radarsat-1 images acquired every 24 d. The InSAR time-series allows to measure slip rates along normal faults with an order of magnitude lower than 1 mm yr -1 . Until the treatment of the SAR images from the new satellite Sentinel-1, acquired every 12 d, which will provide important constraints on the surface velocity map, GPS presently appears to be the more appropriate technique to accurately quantify the low surface strain in Afar, and required a dense network of measurement sites in order to satisfactorily describe both distributed and localized deformation.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…This concerned sites located near the dyking 2005-2010 intrusions in the MH-D segment (KOCA, EWCA, CHIF, K103, KM74, GAGI, SM02 and SM03). For sites located at the southern tip of the segment (HARS, SERD, SOR1, SOR2, SOR3 and TNDH), we only rejected data in the time-series acquired during the co-dyking period (see Grandin et al 2009Grandin et al , 2011Hamling et al 2009;Belachew et al 2011). The whole set of velocities are used for the strain tensor inversion presented in Fig.…”
Section: Derivation Of the Strain Rate Fieldmentioning
confidence: 99%